Influence of post heat treatment on tribological and microstructural properties of plasma wire arc additive manufactured maraging steels - Kaya, Esad; Ulutan, Mustafa; Cakir, Ersin; Buytoz, Soner (Walter de Gruyter Gmbh, 2024)
Metallic alloys are increasingly being produced using wired arc additive manufacturing (WAAM). In this study, 18Ni300 defect-free maraging steels were produced using the WAAM technique. A traditional solution treatment, direct aging, and cryogenic heat treatment processes were applied to the WAAM produced maraging steels. The influence of conventional and novel cryogenic heat treatments on microstructural, mechanical, and tribological properties were examined. The microstructure of the as-built materials obtained by WAAM thermal cycling has mainly been homogenized through the solution, direct-aging, and cryogenic heat treatments. As a result, homogeneously distributed precipitate phases were obtained and the hardness increased by 30 % with a combination different post heat treatments. The cryogenic heat treatment improved the martensitic transformation and facilitated the formation of various Fe-Ni-Mo-Ti-containing intermetallic precipitates. Similarly, because of the different heat treatments, the wear resistance improved by a factor of 2-5.5 relative to the as-built material. Adding the cryogenic heat treatment to the traditional heat treatment procedure improves wear resistance by a factor of 1.2-2.9.
Keywords: WAAM; maraging steel; cryogenic heat treatment; wear; friction